Macromolecular Monomers for the Synthesis of Hydrogel Niches and Their Application in Cell Encapsulation and Tissue Engineering - Nuttelman, Charles R. (2008)
Hydrogels formed from the photoinitiated, solution polymerization of macromolecular monomers present distinct advantages as cell delivery materials and are enabling researchers to three-dimensionally encapsulate cells within diverse materials that mimic the extracellular matrix and support cellular viability. Approaches to synthesize gels with biophysically and biochemically controlled microenvironments are becoming increasingly important, and require strategies to control gel properties (e.g., degradation rate and mechanism) on multiple time and size scales. Furthermore, biological responses of gel-encapsulated cells can be promoted by hydrogel degradation products, as well as by the release of tethered biologically relevant molecules.